Digital economy and institutional dynamics: striving for equitable public service in a digitally transformed era - Lyu, Yuwen; Xie, Junxian; Meng, Xulei; Wang, Xiang (Frontiers in Public Health, 2024)
Background: The rapid emergence of China's digital economy has sparked profound interest in the complex interplay between digitalization and the provision of public services. This study aims to delve deeper into how the development of the digital economy impacts the level of equalization in public service delivery and evaluates whether institutional factors can moderate this transformation. Against the backdrop of pursuing "common prosperity," this research provides valuable guidance for policymaking and strategic planning. It ensures that the ascent of the digital economy not only elevates the standards of public services but also fosters their equitable distribution, thereby advancing the cause of social equity.